(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
To obtain a good harvest, regular pruning of fruit trees and bushes is necessary, which results in the accumulation of piles of cut twigs. These twigs are underutilized and form a large number of agricultural waste. Finding a use for this lignocellulosic biomass is necessary for the sustainable use of resources, as well as for creating additional income for berry growers and rural workers. The purpose of the research was to evaluate the potential of branches of various fruit trees and shrubs as a source of valuable oligomeric polyphenolic compounds – proanthocyanidins, which have a wide range of biologically active properties, including antioxidant, antibacterial, anti-inflammatory, anticancer, etc. Hydrophilic extracts of twigs of sea buckthorn (Hippopae rhamnoides L.), black chokeberry (Aronia melanocarpa), black currant (Ribes nigrum L.), red currant (Ribes rubrum), gooseberry (Grossulariaceae), quince (Cydonia oblonga), raspberry (Rubus L.), and grape (Vitis vinifera) were studied for the first time. The main process for isolating proanthocyanidins from the twigs is the extraction by ethanol-water solutions. The amount of extractive substances in the branches containing proanthocyanidins varied from 6 to 28% per DM. The highest content of proanthocyanidins was found in black chokeberry, quince, and sea buckthorn. The proanthocyanidins isolation from hydrophilic extracts was carried out by Sephadex LH-20. The antimicrobial activity of dominant hydrophilic extracts and purified oligomeric proanthocyanidins was studied against eleven pathogenic bacteria and fungus: Pseudomonas syringae pv. syringae, Erwinia rhapontici, Fusarium culmorum, Verticillium dahlia, Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Bacillus cereus, Candida albicans and Cutibacterium acnes. The MIC and MBC/MFC of extracts ranged from 2 to 6 mg/mL. The antimicrobial activity of purified proanthocyanidins was 10 times higher than that of the extracts.